Dosimetric Comparison of VMAT Alone and VMAT with HDR Brachytherapy Boost Using Clinical and Biological Dose Models in Localized Prostate Cancer - Manuel Guhlich; Olga Knaus; Arne Strauss; Laura Anna Fischer; Jann Fischer; Stephanie Bendrich; Sandra Donath; Leif Hendrik Dröge; Martin Leu; Stefan Rieken; Annemarie Uhlig; Markus Anton Schirmer; et al. (Current Oncology, 2025)
Background: Combining external beam radiotherapy (EBRT) with high-dose-rate (HDR) brachytherapy (BT) enables biologically effective dose escalation in prostate cancer. However, comparative evaluation of such regimens using radiobiological modeling remains limited. Methods: Dose regimens based on clinical practice were analyzed using α/β values of 1.5 and 3 Gy for the prostate. Ten patients with available planning CT, pelvic MRI, and ultrasound-guided BT plans were retrospectively evaluated. Physical and biological dose distributions were recalculated for various EBRT and HDR-BT combinations. Biological effective dose (BED) values were determined for the prostate and organs at risk (OARs: anterior rectal wall, bladder base, urethra). Regimens yielding the highest ΔBED between prostate and OARs were considered most favorable. Results: All regimens met clinical dose constraints. The most favorable ΔBED profiles for bladder and rectum were observed with HDR-BT regimens (2 × 15 Gy) combined with either 23 × 2 Gy or 15 × 2.5 Gy EBRT, independent of the assumed α/β value. EBRT-only regimens achieved superior urethral sparing, while higher HDR doses led to increased urethral exposure. Conclusions: This study underscores the value of radiobiological modeling in differentiating and optimizing prostate cancer radiotherapy strategies. While the trade-offs between dose escalation and OAR sparing are clinically known, our biologically driven analysis provides a more quantitative foundation for selecting and tailoring combined EBRT/HDR-BT regimens in practice.